Geen makke schapen: Loonpolitiek, vakbonden en ‘wilde’ stakingen in de aanloop naar de loonexplosie van 1964 - Knotter, Ad (TSEG - The Low Countries Journal of Social and Economic History, 2021)
‘No flock of gentle sheep’. Wage policies, trade unions, and unofficial strikes in the Netherlands in the run up to the wage explosion of 1964. In 1964, the Netherlands experienced an average gross wage increase of 17 percent. In the economic literature, this wage explosion is mostly explained by the contrast between labour market developments and the restrictive wage policies by the Dutch government, which until that year adhered to central, state led wage determination. Overfull employment pressured employers to circumvent and ignore government regulations, and induced trade unions to increase wage demands, which, under labour market pressure, in 1963/64 were easily and willingly met by both employers and the government. In this article, it is argued that this explanation is too one sided, as it only takes marketplace bargaining power of workers into account (the power that results directly from tight labour markets), and ignores associational power (the power that results from the formation of collective organizations of workers). Focussing on unofficial strikes in the metal industries between 1959 and 1963, it is shown that in the run up to the wage explosion, tensions between rank and file and union leadership increased, which eventually forced the leaders to change their attitude. Remnants of the post-war, but now dissolved, communist trade union ‘Eenheidsvakcentrale’ in the Amsterdam shipbuilding industry played a pivotal role in the mobilisation for these wildcat strikes.